Physical and Electrical Properties of Zinc-Magnesium-Phosphate Glasses - Ng, Beng Hong (2007)
Glasses in a wide range of composition in the ternary system x(ZnO)-y(MgO)-z(P2O5) where x ranges from 5 to 20 mol %, y ranges from 5 to 20 mol % and z ranges from 50 to 70 mol % have been prepared by traditional melt quenching technique with ZnO, MgO and P2O5 as the starting raw materials. X-ray diffraction (XRD), refractive index and electrical properties have been used to characterize the structural, optical and electrical features. All the sample glasses at present work have been confirmed to be amorphous by X-ray diffraction technique using Philips Model 7602 EA Almelo. The refractive indices of ternary glasses were measured by Ellipsometer and were found to agree with Lorentz-Lorenz equation where the refractive index increased with the increase of the density (ρ) and the decrease of the molar volume (Vm) of the glass. The density of the glass was determined by Archimedes Principle. From the empirical data, other values such as molar volume and molar refractivity have been computed. The variations in the molar volume were resulting in variation on the density and refractive index of the glasses. From the results obtained, it is obvious that the refractive index varies with molar refractivity, which depends on the polarizability of the ions, density and molecular weight in the sample glass. Those physical properties were found to be sensitively depending on its composition. Electrical conductivity (σ) was measured in the temperature 30 oC to 300 oC. Conductivity for the ternary series glasses increased with addition composition of ZnO or MgO with temperature. Activation energy (Ea) was calculated by the slope of graph log σ versus 1000/T with Arrhenius equation. The values of activation energy in the ternary series were recorded in the range of 0.023 eV to 0.112 eV.